Ride-hailing users are likely early adopters of shared micromobility in mid-sized cities of developing countries: A case study of Kathmandu, Nepal - Nitesh R. Shah; Saurav Parajuli; Christopher R. Cherry (Journal of Cycling and Micromobility Research)
While shared micromobility has been gaining popularity in developed countries, these innovative technologies have yet to penetrate the market of mid-sized cities in developing countries, which make up the overwhelming majority of cities in the world. Shared micromobility includes inexpensive systems that could drive the first wave of electrification in the transportation sector in these regions. We designed and implemented a dynamic stated preference pivoting survey and used a panel data mixed logit model to assess the effect of temperature, precipitation, and availability of bike lanes on the propensity to use bikeshare, e-bike share, and e-moped share, controlling for sociodemographic factors. Using Kathmandu, Nepal, as a case study, where shared micromobility does not currently exist, we also assessed modal shifts from the existing travel modes. We found heavy rain negatively impacts users’ preference for shared micromobility, while users preferred e-moped share during cold temperatures. The effect of bike lane availability was positive but weak on bikeshare and e-bike share. Gender also had an effect on the choice of shared micromobility vehicles – females preferred e-mopeds over other vehicles. Ride-hailing users had a high preference for e-moped share, while introducing bikeshare and e-bike share caused a uniform modal shift among existing travel modes. We recommend that transportation agencies begin micromobility pilot programs by combining this study’s findings with the best practices of existing micromobility programs. We also suggest collecting usage and operations data to empower data-driven decision-making.